A transnational history of the World War I in Jay Winter’s research - Hlibischuk, Nikolai V. (Journal of the Belarusian State University. History, 2020)
Based on the example of the scientific research of the famous american historian Jay Winter, the transnational approach and its advantages in the study of the World War I were analyzed in the article. The attention is paid to the characteristics of this method and its features. According to Jay Winter, transnational dimension of the Great War of 1914–1918 allows to go beyond the narrow national narrative and look at it from the new position, the questions which were studied a long time ago can be inserted in the broad global context and to rethink the meaning and consequences of this global conflict. The author also tried to outline the research perspectives and opportunities which are open in applying this approach.
Keywords: World War I; transnational approach; Jay Winter; Western historiography